Cathode recovery products of oxidation of oils - Захарчук, М.М.; Ледовських, В.М. (Proceedings of National Aviation University (archive), 2009)
The article provides the review of electrochemical reduction of carbonic compounds – those that are among main oxidation of oils hydrocarbons products. The principal possibility of ketons to alcohols reduction is proved in practice based on the experimental data . The methodical algoritm of quantative control of the catod reduction is developed, which uses the reduction-oxidizing potentiometric titration method.